Determinants of Audit Report Lag of Financial Statements in Banking Sector - Sigit Handoyo; Erza Diandra Maulana (Faculty of Economics and Business Udayana University, 2019)
Audit Report Lag (ARL) is the time length of the auditor completing their activities on the client is measured from the end of the fiscal year until the date of audit report was signed. Research related to ARL has been widely carried out in some countries, considering the importance of this issue. This study analyzed the factors that affect ARL on the Conventional Bank Companies listed in the Indonesia Stock Exchange. The sample consisted of 84 companies listed in Indonesia Stock Exchange (IDX) which submitted financial reports to OJK (the Financial Service Authority) in the period of 2013-2015. The data used in this research was selected by using purposive sampling method and analysis used multiple linear regression. Based on the analytical results, Profitability, Auditor Opinion, and Firm Reputation had negative significant effect toward ARL. Then Auditor Switching, Complexity, and Board of Size of Director had positive significant effect toward ARL.